Representation of Sapardi Djoko Damono’s Poetry in Islamic Education; A Semiotic Study - Anggreini, Heny (The Pontianak State Institute of Islamic Studies, 2019)
The poetry analyzed are “Hatiku Selembar Daun”, “Yang Fana Adalah Waktu”, and “Akulah Si Telaga”. The poetry are analyzed using qualitative research methods, which are analyzed descriptively through words, lines, and verses, using Roland Barthes's semiotic theory. The results of this study explain that the myth that Barthes interpreted as an ideology delivered by poets in his poetry to instill the view of Islam in living life because of moral degeneration that occurs in humans today. Through the poetry, the poet contests his ideology about attitudes and traits that must be possessed by humans based on the teachings of Islam, that: First, humans are very fragile creatures. Second, there is no eternity on this earth. Third, sacrifices that do not ask for rewards or profit.